Encyclopedia of Africa, Volume 1 - Appiah, Anthony; Gates, Henry Louis, Jr. (Oxford ; New York : Oxford University Press, 2010)
"The Encyclopedia of Africa focuses on African history and culture with articles that cover prominent individuals, events, trends, places, political movements, art forms, business and trade, religions, ethnic groups, organizations, and countries throughout Africa"--Provided by publisher.
List of maps, charts, and tables -- Introduction -- Acknowledgments -- Chronology of selected events -- Map of Africa -- Encyclopedia of Africa -- Contributors, volume 2 -- Topical outline of selected entries -- Bibliography, volume 2 -- Index, volume 2.
Includes bibliographical references (v. 2, pages 587-589) and index.
Keywords: Histoire; Politique; Biographies; Dictionnaires; Africa -- Encyclopedias; Afrique; Africa; Afrika; Afrika -- 2; Afrika; Afrique -- 2; Encyclopedias; Nonfiction; Encyclopedias